Credibility versus fake news in digital newspapers on tablets in primary education / Credibilidad versus falsedad de las noticias de periódicos digitales sobre la tableta en la Educación Primaria. Issue 2 (3rd April 2019) - Ricoy, María-Carmen; Sánchez-Martínez, Cristina; Feliz-Murias, Tiberio
Abstract: The press is often attributed with little credibility, and the recent phenomenon of fake news has put it under the spotlight once again. As a result, the objective of this study is to discover the margin of the veracity versus falsehood of the news reports on tablets in primary education published in digital newspapers. This qualitative study has been developed on the basis of an analysis of 120 news items in Spanish newspapers. The conclusions show that news items on the topic correspond with reality and can be considered credible since they are in line with results provided in the scientific literature. Nevertheless, and in accordance with this type of publication, the treatment of the topic in these news items is superficial, even though they usually dedicate a full page to it. When discussing benefits and controversial points, both newspaper articles and scientific studies highlight the immediacy offered by tablets and the motivation generated in students. At the same time, their use is also linked with harmful effects associated with technopathologies.